Modulatory influence of Avocado on renal oxido - Lipidemic stress and mRNA expression of NOS in renal artery studied in nephropathy induced rats - U. S., Mahadeva Rao; Keshav, Kumar; Jegathambigai, Rameshwar Naidu (2014)
Objective: The present study was designed to assess the beneficial effects of alcoholic (ethanol) extract of fruit of Avocado (AEFA) on biochemical, histological, and gene expression study in hypercholesterolemic diet fed nephropathy induced albino rats. Experimental design: Avocado fruit pulp was extracted with 90% ethanol, finally filtered and dried. Group-I rats as control, Group-II fed with hypercholesterolemic diet (HCD) for 45 days [4% cholesterol and 1% cholic acid], Group-III fed with HCD for 45 days + AEFA (300 mg/kg body weight/day orally) for last 30 days and Group-IV fed with AEFA alone. Collection of blood and excision of kidney were done for various biochemical and histological analysis. Result: The levels of total cholesterol (TC), triacylglycerol (TG), phospholipids (PLs), renal markers (serum urea, creatinine and uric acid) and renal lipid peroxidation (LPO) products were markedly mitigated in AEFA treated hypercholesterolemic rats. FRSA factors were significantly increased, on supplementation with AEFA. Administration with AEFA, the mRNA levels of eNOS and iNOS genes was expressively up-regulated and down-regulated. Histomorphological observations shown that, AEFA admirably protects the renal tissues from hypercholesterolemia - mediated oxido-lipidemic damage. Discussion and conclusion: From this study it was conjectured that AEFA can act as nephroprotective agent by attenuating the serum lipid profile, renal oxidative stress, besides regulating the mRNA expression of NOS in renal artery.